2009
DOI: 10.1128/iai.00565-09
|View full text |Cite
|
Sign up to set email alerts
|

The Trehalose Synthesis Pathway Is an Integral Part of the Virulence Composite for Cryptococcus gattii

Abstract: The trehalose pathway is essential for stress tolerance and virulence in fungi. We investigated the importance of this pathway for virulence of the pathogenic yeast Cryptococcus gattii using the highly virulent Vancouver Island, Canada, outbreak strain R265. Three genes putatively involved in trehalose biosynthesis, TPS1 (trehalose-6-phosphate [T6P] synthase) and TPS2 (T6P phosphatase), and degradation, NTH1 (neutral trehalose), were deleted in this strain, creating the R265tps1⌬, R265tps2⌬, and R265nth1⌬ muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
93
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 56 publications
3
93
1
Order By: Relevance
“…The second perspective relies on the urgent need for new antifungal therapies. The trehalose synthase pathway is widespread in the fungal kingdom where it can be part of the virulence system (23,(67)(68)(69), thus making Tps1 a potential antimicrobial target for weakening mammalian and plant pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The second perspective relies on the urgent need for new antifungal therapies. The trehalose synthase pathway is widespread in the fungal kingdom where it can be part of the virulence system (23,(67)(68)(69), thus making Tps1 a potential antimicrobial target for weakening mammalian and plant pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, Wilson and colleagues showed in Magnaporthe that control of nitrogen metabolism and pathogenicity was integrated with trehalose metabolism; Tps1 is required for proper regulation of the nitrogen repressor NMR1 (12). The latter finding is intriguing, as recent data regarding the NMR1 homolog TAR1 in C. neoformans demonstrate the relationship of nitrogen regulation to melanin production, which is a major virulence factor for C. neoformans (13), and the trehalose pathway has signal control on the cryptococcal virulence composite (14,15).…”
mentioning
confidence: 92%
“…Several studies have shown that C. neoformans and C. gattii, share the same key virulence factors already known [139,140], although there are reports that some virulence attributes are specific for each species [141][142][143][144]. In this context, it can be mentioned that superoxide dismutase (Sod1, a prominent antioxidant) is required for virulence of C. gattii, but not for C. neoformans [145].…”
Section: Cryptococcosismentioning
confidence: 99%